EFEKTIVITAS PENERAPAN PEMBELAJARAN BERBASIS SETS TERHADAP HASIL BELAJAR SISWA SMPIT NURUL WAHDAH PONTIANAK - Hanif Riffalah; Erlina Erlina; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe aims of this research were to determine students’ learning outcome before and after the learning application based on Science, Environment, Technology and Society (SETS) and to assess the effectiveness of learning application based on SETS towards grade eighth students’ learning outcome of SMPIT Nurul Wahdah Pontianak. The form of this research was preexperimental design with one-group pre-test-post-test design. The subject of this research was 31 students of grade eighth. Data collection technique were measurement, direct communication, and observation. The collected data were analyzed using normality test with Shapiro-Wilk test. The normality test result showed that the Sig. values of pre-test and post-test were more than 0.05 which means that data were distrubuted normally. The result of hypothesis test using Paired Sample T-Test showed that Sig. (2-Tailed) value were 0.000 which is less than 0.05. It means that there are differences between pre-test and post-test result. The learning application based on SETS effective enough to increase the students' learning outcome with N-Gain interpretation by 74%.Keywords: Effectiveness, Learning Outcome, SETS